Thermal Conductivity of Buckled and Puckered Arsenene: An Equilibrium Molecular Dynamics (EMD) Simulation - Calo , Ferdinand Michael; Lazarte , Jessa Mae; Bedrijo, D’Lanor Rose (International Journal of Membrane Science and Technology, 2023)
This study aims to calculate the thermal conductivity of buckled and puckered arsene using Molecular Dynamics simulation through Large-scale Atomic/Molecular Massively Parallel Simulation (LAMMPS). Arsenene is the monolayer of arsenic, that belongs to one of its allotropes, the gray metallic arsenic. The temperature varied from 100K, 300K, 500K, and 700K with a fixed dimension of 10nm x 50nm. Also, the length of the material varied from 10nm, 20nm, and 30nm. 40nm and 50nm at a fixed temperature of 300 K with constant width of 10nm. Results show that the main contributor to the increase of thermal conductivity is due to the phonon means free path. As the length increases, the thermal conductivity also increases because of its long mean free path. Moreover, the decreasing thermal conductivity as to the increase in temperature is due to phonon mean free path shrinking, resulting in a reduction in thermal conductivity. At room temperature, the thermal conductivity of buckled and puckered arsenene is found to be 1.8 W/mK and 1.3 W/mK, respectively. This study will provide fresh insight into the thermal properties of buckled and puckered arsenene, which will be useful for nanoelectronics applications.